a)căn 3 sin4x-cos4x-2cosx=0
b)cosx +căn 3 cos2x-căn 3 sinx-sin2x=0
c)cos 3x+sin2x=căn 3(sin3x+cos2x)
d)cosx +căn 3=3-3/cosx+căn 3 sinx+1
(sin2x+cos2x)cosx+2cos2x-sinx=0
\(\dfrac{cos2x-sinx-cosx+2}{sinx-1}=0\)
Giải phương trình: sin2x-cos2x+3sinx-cosx -1=0
giải phương trình
1.\(sin^3x+2cosx-2+sin^2x=0\)
\(2.\frac{\sqrt{3}}{2}sin2x+\sqrt{2}cos^2x+\sqrt{6}cosx=0\)
3.\(2sin2x-cos2x=7sinx+2cosx-4\)
4.\(2cos2x-8cosx+7=\frac{1}{cosx}\)
5.\(cos^8x+sin^8x=2\left(cos^{10}x+sin^{10}x\right)+\frac{5}{4}cos2x\)
6.\(1+sinx+cos3x=cosx+sin2x+cos2x\)
7.\(1+sinx+cosx+sin2x+cos2x=0\)
Giải phương trình sin2x-cos2x+5sinx-cosx-2=0
1> 1 + sinx + cosx + sin2x + cos2x = 0
2> cos2x + 3sin2x + 5 sinx - 3cosx = 3
3> \(\dfrac{\sqrt{2}*(cosx - sinx)}{cotx - 1}\) = \(\dfrac{1}{tanx + cot2x}\)
4> (2cosx - 1)*(2sinx + cosx) = sin2x - sinx
1) cos3x - cos4x + cos5x =0
2) sin3x + cos2x = 1 + 2sinx.cos2x
3) cos2x - cosx = 2 sin\(^2\)\(\dfrac{3x}{2}\)
4) cos\(^2\)2x + cos\(^2\)3x = sin\(^2\)x
5) sin3x.sin5x - cos4x.cos6x = 0
\(cos2x+cosx-\frac{\sqrt{2}}{2}=0\)
6. giai pt
1+sinx+cosx+sin2x+cos2x=0